Evaluation of TPS 3R and Waste Bank Management in Sungai Penuh City - Rahmadhani, Fitra; Aziz, Rizki; Indah, Shinta (Universitas Negeri Padang, 2024)
Sungai Penuh City has 16 units of TPS 3R and 1 unit of waste bank that are not operating optimally. The evaluation to determine the condition of TPS 3R and waste bank and the potential reduction obtained if they are operated again. The research began by collecting data on generation of solid waste, composition, and recycling possibilities for household waste. Sampling of waste generation based on SNI 19-3964-1994 in 8 sub-districts in Sungai Penuh City for 8 consecutive days with the household generation of solid waste outcome of 0.328 kg/person/day or 2.789 l/person/day. The composition of household waste in Sungai Penuh City includes 57.74% food waste, 14.38% plastic waste, 11.62% paper waste, 5.19% yard waste, 4.89% other waste, 2.79% glass waste, 2.16% fabric waste and 1.24% metal. Sungai Penuh City has the capacity to recycle household solid waste is 68.90%. TPS 3R and waste bank was evaluated based on the Technical Guidelines for TPS 3R of The Ministry of Public Works and Housing in 2023 and the Regulation by the Minister of Environment and Forestry Number 14 of 2021. The evaluation results show that 3 units of TPS 3R are in the medium category, 4 units of TPS 3R are in the less category and 9 units of TPS 3R are in the bad category. Meanwhile, waste bank is in the bad category. The potential for waste reduction by TPS 3R and waste bank if operated optimally is 23.26% of the total waste generated in Sungai Penuh City.